Pengembangan E-Service Jasa Pernikahan Pada Marni Wedding Organizer Dengan Metode RAD - Muhammad Alwan Nurdin; Vihi Atina; Faulinda Ely Nastiti (Computer Science Research and Its Development Journal, 2024)
In the digital era, Wedding Organizer (WO) services have become increasingly vital in facilitating wedding planning and execution. However, many WOs, including Marni Wedding Organizer, still grapple with inefficiencies stemming from manual operational systems. This research endeavors to address this issue by developing a web-based e-service system for Marni Wedding Organizer using the Rapid Application Development (RAD) method. RAD was chosen for its iterative approach and adaptability to evolving requirements. The system, developed using PHP, JavaScript, MySQL, and the Midtrans API, progresses through phases of requirements analysis, system design, coding, and testing. The study identifies operational inefficiencies as the primary problem, prompting the need for technological intervention. Through thorough testing, the system achieves a 100% testing level across all modules, ensuring robust functionality. However, limitations exist in the system's scope, focusing solely on booking and payment processes. Future research could explore expanding system features for enhanced service personalization. Ultimately, the developed e-service system enhances operational efficiency, customer satisfaction, and resource management for Marni Wedding Organizer.